DEFOLIADORES DE ENCINAR EN EL ANDÉVALO OCCIDENTAL DE LA PROVINCIA DE HUELVA. COMPARACIÓN ENTRE DOS SITUACIONES PUNTUALES: EL PERIODO 1985-1988 Y EL AÑO 2000 - Granados, C; Ramírez, D; Sánchez, I; López, G; Vázquez, E (III Congreso Forestal Español, 2001)
The great economic and ecological importance of holm oak (Quercus ilex L.) in Spain makes necessary to study the presence and repercussion of leaf-damaging insects in holm oak forests. The field study has been carried out in “Los Millares”, one property of Andévalo Occidental (southern Spain, Andalusia, Huelva). This zone was chosen for two reasons: the existence of previous data about the presence and evolution of leaf-damaging insects during the period 1985-1988, fruit of the work of F.J. Toimil and collaborators; as well as the certainty that this year the population of this insects was very high. The results showed that Tortrix viridana, Archips xylosteana, Periclista andrei and, on a smaller scale, Catocala nynphagoga y Dryobotodes eremita constitute at the moment the main leaf-damaging insects, representing more than 87% of the leaf-damaging found. This population can cause big damages in the holm oak forests, with important economic and ecological losses
Keywords: Andévalo; Huelva; leaf-damaging Quercus ilex; Tortrix viridana

Efecto de las inyecciones de fosfonato potásico en tronco de encina (QUERCUS ILEX SUBSP. BALLOTA) SOBRE EL CRECIMIENTO DE RAMILLAS Y LA FRUCTIFICACIÓN. - CORDÓN, S; BRAVO, V; TAPIAS, R; López, G; Sánchez, I (III Congreso Forestal Español, 2001)
The present communication intends to see the answer of the oaks (Quercus ilex subsp. ballota) treateds using antifungal materials (potassium phosphonate) injections to the trunk. In the first year, has been measured the growth of the buds and the production of acorns of three treated oaks and other three not treated, in one property of the Western Andévalo (Andalusia, Huelva).
Keywords: Andévalo; Huelva; Quercus ilex; trunk injections

BREEDING ECOLOGY OF THE BLUE TIT PARUS-CAERULEUS IN EASTERN SPAIN - A COMPARISON WITH OTHER LOCALITIES WITH SPECIAL REFERENCE TO CORSICA - GILDELGADO, J A; López, G; BARBA, E (ORNIS SCANDINAVICA, 1992)
Aspects of the breeding ecology of the Blue Tit Parus caeruleus were studied in intermediate stages of succession in a holm oak forest at Monte Poblet (eastern Spain) from 1985 to 1991. In different years the density in two plots without nest-boxes varied between 1.0 and 6.5 pairs per 10 ha. Nestbox introduction seems to have increased the density of breeding pairs. The mean laying date was earlier (6 vs. 13 May) in low altitude (500-750 m a.s.l.) plots than in a high altitude (900-1000) m a.s.l.) plot, but clutch size (6.9 vs. 6.5 eggs) was not significantly different (mean 6.6 eggs). No differences in mean laying dates were found between years. Significant differences in clutch size were found only between two years at the high altitude site. There was a slight, non-significant, seasonal decline in clutch size. No second clutches were laid. These results are discussed in the context of other Mediterranean studies with special focus on the differences and similarities between Corsican and mainland populations. It is shown that most of the characteristics of the Corsican population (i.e. density, habitat use, laying date, clutch size, number of broods per year) are shared by some populations on the mainland. On the other hand, some breeding traits of Blue Tit populations in southern France are closer to those of Central and North European populations than to the Iberian ones.
APS
Keywords: Blue tit; breeding ecology; Holm oak forest; nest-boxes; Parus cearuleus; Spain; succession stages